Impact of Host and Management Factors on Calf Morbidity and Mortality Rates in Smallholder Dairy Farms in Central Ethiopia: A Prospective Cohort Study - Biruk Alemu; Gizachew Hailegebreal; Rahmeto Abebe (Veterinary Medicine International, 2025)
The dairy sector in Ethiopia is vital for the agricultural economy and smallholder farmers; however, calf morbidity and mortality present significant challenges. A prospective longitudinal study conducted tracked 204 newborn calves across 120 farms in central Ethiopia to estimate morbidity and mortality rates, identify causes, and assess risk factors. The calves were monitored every 15 days until they reached 6 months of age. Data analysis utilized Kaplan–Meier survival analysis and Cox proportional hazard regression. The study found a morbidity rate of 13.4 and a mortality rate of 4 cases per 100 calf-months at risk. Diarrhea was the most commonly diagnosed condition, accounting for 50.5% of morbidity and 64.5% of mortality. Key risk factors for morbidity included calving assistance (HR = 1.93), floor structure (HR = 2.88), calf sex (HR = 1.86), late colostrum intake (HR = 1.7), weaning age (HR = 0.47), dam breed (HR = 0.21), and calf age (HR = 0.23). Risk factors for mortality included farm location (HR = 0.25), calving assistance (HR = 7.7), birth site (HR = 27.3), floor structure (HR = 9.18), late colostrum intake (HR = 7.68), weaning age (HR = 0.03), and calf age (HR = 0.15). The observed morbidity and mortality rates exceed acceptable levels, jeopardizing calf health and dairy sector growth. Enhancing management practices—such as timely colostrum provision, early disease detection and treatment, and farmer education—is crucial to mitigate these rates. Further research is needed to pinpoint specific causes of calf morbidity and mortality in the study areas.